2012
DOI: 10.5194/acp-12-10077-2012
|View full text |Cite
|
Sign up to set email alerts
|

BVOC-aerosol-climate interactions in the global aerosol-climate model ECHAM5.5-HAM2

Abstract: The biosphere emits volatile organic compounds (BVOCs) which, after oxidation in the atmosphere, can partition on the existing aerosol population or even form new particles. The large quantities emitted provide means for a large potential impact on both aerosol direct and indirect effects. Biogenic responses to atmospheric temperature change can establish feedbacks even in rather short timescales. However, due to the complexity of organic aerosol partitioning, even the sign of these feedbacks is of large uncer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 64 publications
0
59
1
Order By: Relevance
“…The volatility assumed for the SOA in atmospheric models significantly affects the way this condensing material modifies the atmospheric aerosol size distribution (see, e.g., Riipinen et al, 2011;Donahue et al, 2011;Zhang et al, 2012b). Current atmospheric large-scale models differ considerably in the ways they treat the condensation of SOA: some assign the SOA a range of volatilities but assume it to be in thermodynamic equilibrium (Yu and Luo, 2009), while others assume the SOA to be completely nonvolatile (Spracklen et al, 2005a, b;Pierce and Adams, 2009;Makkonen et al, 2012). The former approach tends to underestimate the growth of freshly-formed nanoparticles (and thus their contribution to CCN), while the latter is expected to somewhat overpredict it if the total SOA is correctly predicted by the model .…”
Section: S a K Häkkinen Et Al: Semi-empirical Parameterization Ofmentioning
confidence: 99%
“…The volatility assumed for the SOA in atmospheric models significantly affects the way this condensing material modifies the atmospheric aerosol size distribution (see, e.g., Riipinen et al, 2011;Donahue et al, 2011;Zhang et al, 2012b). Current atmospheric large-scale models differ considerably in the ways they treat the condensation of SOA: some assign the SOA a range of volatilities but assume it to be in thermodynamic equilibrium (Yu and Luo, 2009), while others assume the SOA to be completely nonvolatile (Spracklen et al, 2005a, b;Pierce and Adams, 2009;Makkonen et al, 2012). The former approach tends to underestimate the growth of freshly-formed nanoparticles (and thus their contribution to CCN), while the latter is expected to somewhat overpredict it if the total SOA is correctly predicted by the model .…”
Section: S a K Häkkinen Et Al: Semi-empirical Parameterization Ofmentioning
confidence: 99%
“…The BSOA affects climate directly by scattering solar radiation and indirectly by aerosolcloud interactions (e.g. Makkonen et al, 2012). The latter effect is tied strongly with atmospheric cloud condensation nuclei (CCN) production, and thereby also with atmospheric new particle formation and growth Yu, 2011;Kerminen et al, 2012;Makkonen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MEGAN2 was run offline and its output data were used for the ECHAM-HAM input initialization. More details can be found in Makkonen et al (2012).…”
Section: Aerosol Schemesmentioning
confidence: 99%
“…Previous studies have shown that the implementation of an activation-type nucleation improves particle number concentration estimations in modeling (Spracklen et al, 2010;Makkonen et al, 2012). In our experiment, we coupled a binary sulphuric acid-water nucleation scheme (Vehkamäki et al, 2002) with an activationnucleation scheme described by Paasonen et al, (2010, Eq.…”
Section: Aerosol Schemesmentioning
confidence: 99%
See 1 more Smart Citation